PENGARUH K3 DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. DWI LESTARI NUSANTARA - Julius Simbolon; Nuridin (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2017)
The purpose of this study is to determine how relationship and influence of safety, occupationalhealth and work environment to employees performance at PT. Dwi Lestari. The research method was usedwith explanatory analysis approach that is explaining the causalistic relationship between variables.Technique of data analysis was used by finding regression and correlation, determination coefficient andhypothesis test, but before it was analyzed, first was done instrument test of research data. Results of thisresearch was obtained there is relationship and positive influence and significant between safety variables,occupational health and work environment to employees performance at PT. Dwi Lestari Nusantara by usingF test. F test was used to test the feasibility of model in research. Results the trial fo F test showed thatregression model can be used to predict employees performance. Test result of t test showed that safety,occupational health have positive and significant influence to employees performance, and work environmenthave positive and significant influence to employees performance at PT. Dwi Lestari Nusantara. Whilesafety, occupational health were variables which is very dominant and influence to employees performance atPT. Dwi Lestari Nusantara. Conclusion, there is a positive and significant influence between safety variables,occupational health and work environment to employees performance at PT. Dwi Lestari Nusantara